A combination of single nucleotide polymorphisms is associated with the interindividual variability in the blood lipid response to dietary fatty acid consumption in a randomized clinical trial. Issue 2 (19th April 2021) - Rajendiran, Ethendhar; Lamarche, Benoît; She, Yongbo; Ramprasath, Vanu; Eck, Peter; Brassard, Didier; Gigleux, Iris; Levy, Emile; Tremblay, Angelo; Couture, Patrick; House, James D; Jones, Peter J H; et al.
ABSTRACT: Background: Blood lipid concentrations display high interindividual variability in response to dietary interventions, partly due to genetic factors. Existing studies have focused on single nucleotide polymorphisms (SNPs) analyzed individually, which only explain a limited fraction of the variability of these complex phenotypes. Objective: We aimed to identify combinations of SNPs associated with the variability in LDL cholesterol and triglyceride (TG) concentration changes following 5 dietary interventions. Design: In a multicenter randomized crossover trial, 92 participants with elevated waist circumference and low HDL cholesterol concentrations consumed 5 isoenergetic diets for 4 wk: a diet rich in saturated fatty acids (SFAs) from cheese, SFA from butter, monounsaturated fatty acids (MUFAs), n–6 polyunsaturated fatty acids (PUFAs), and a diet higher in carbohydrates (CHO). The association between 22 candidate SNPs in genes involved in lipid and bile acid metabolism and transport and changes in LDL cholesterol and TG concentrations was assessed with univariate statistics followed by partial least squares regression. Results: Endpoint LDL cholesterol concentrations were significantly different (cheese: 3.18 ± 0.04, butter: 3.31 ± 0.04, MUFA: 3.00 ± 0.04, PUFA: 2.81 ± 0.04, CHO: 3.11 ± 0.04 mmol/L; P  < 0.001) while endpoint TG concentrations were not ( P  = 0.117). Both displayed consistently elevated interindividual variability following the dietary interventions (CVs of 34.5 ± 2.2% and 55.8 ± 1.8%, respectively). Among the 22 candidate SNPs, only ABCA1- rs2066714 and apolipoprotein E (APOE) isoforms exhibited consistent significant effects, namely on LDL cholesterol concentrations. However, several SNPs were significantly associated with changes in LDL cholesterol and TG concentrations in a diet-specific fashion. Generated multivariate models explained from 16.0 to 33.6% of the interindividual variability in LDL cholesterol concentration changes and from 17.5 to 32.0% of that in TG concentration changes. Conclusions: We report combinations of SNPs associated with a significant part of the variability in LDL cholesterol and TG concentrations following dietary interventions differing in their fatty acid profiles.